Studies in the reproductive Physiology of the Amphibia - Berk, Lionel (Division of Physiological Sciences, 2024)
The changes occurring in the red blood cells in infective illness are amongst the least carefully studied problems of haematology. In spite of the fact that these anamias are extremely common, it is difficult to find adequate literature to make possible even a clear description of the blood picture under these circumstances. Part of the difficulty is due to the fact that anaemias in infections are grouped together with other anaemia, in which many mechanisms undoubtedly active. Another major source of confusion is the fact that in many of the cases in which "secondary anaemia" occurs, complicating factors such as haemorrhage and liver disease are not adequately dealt with.